Characterisation of the Genetic Mechanism Behind Floral Trichomes in Brassica rapa - Fitzsimons, Christina (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Genetics, 2023)
In his seminal essay ?The Metamorphosis of Plants?, published in the 18th century, Johann Wolfgang von Goethe hypothesized that all above-ground organs of a plant, including floral organs, are derived from leaf-like structures. Over 200 years later, his ideas were confirmed when plants containing mutations for A-, B-, and C-class floral homeotic genes, or all functionally redundant E-class floral homeotic genes, were found to develop flowers that consisted of leaf-like organs with trichomes. Work carried out previously in our laboratory provided insight into the genetic mechanism underlying this metamorphosis, finding that the activities of AGAMOUS (a C-class floral homeotic protein) overlap with the gene network controlling trichome formation; AGAMOUS suppresses their formation on floral organs under normal developmental conditions. When a weak ag mutant allele was combined with mutant alleles of trichome repressor genes, Arabidopsis plants were generated with flowers that developed supernumerary trichomes on the floral organs. Given that trichomes are known to confer protection from pests, it was thought that this mechanism of inducing trichomes to develop on the gynoecium and subsequent seedpod could provide an increased level of innate pest protection. The advantage of this approach is that the highest level of protection is offered to the fruit of the plant which is often the most agriculturally and economically important part of a plant. The main aim of the work described in this thesis was to translate these findings on the regulation of trichome initiation in Arabidopsis flowers, described by ??Maoil?idigh et al. (2018), to Brassica rapa in order to generate plants with supernumerary trichomes as a potential new avenue for crop protection.
APPROVED